2022
DOI: 10.1111/ene.15281
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, neuroimaging correlates and prognosis of the motoric cognitive risk syndrome: A population‐based comparison with mild cognitive impairment

Abstract: Background and purpose This study was undertaken to compare risk factors, neuroimaging characteristics and prognosis between two clinical prodromes of dementia, namely, the motoric cognitive risk syndrome (MCRS) and mild cognitive impairment (MCI). Methods Between 2009 and 2015, dementia‐free participants of the population‐based Rotterdam Study were classified with a dementia prodrome if they had subjective cognitive complaints and scored >1 SD below the population mean of gait speed (MCRS) or >1.5 SD below th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
(73 reference statements)
3
20
0
2
Order By: Relevance
“…A recent study comparing MCR and MCI found many shared risk factors but also noted that differences in gender, hypercholesterolaemia, BMI, and cerebral white matter volumes indicate different pathophysiological substrates 38 . This study also reported that MCR captured early features of dementia in the absence of MCI 38 …”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…A recent study comparing MCR and MCI found many shared risk factors but also noted that differences in gender, hypercholesterolaemia, BMI, and cerebral white matter volumes indicate different pathophysiological substrates 38 . This study also reported that MCR captured early features of dementia in the absence of MCI 38 …”
Section: Discussionmentioning
confidence: 58%
“…37 A recent study comparing MCR and MCI found many shared risk factors but also noted that differences in gender, hypercholesterolaemia, BMI, and cerebral white matter volumes indicate different pathophysiological substrates. 38 This study also reported that MCR captured early features of dementia in the absence of MCI. 38 This is the first study to explore the overlap of MCR and Frailty according to Fried phenotype (characterised as the presence of five components: weakness, slowness, exhaustion, low physical activity, and unintentional weight loss).…”
Section: Overlap Of Mcr MCI Prefrailty and Frailtymentioning
confidence: 53%
See 2 more Smart Citations
“…Previous studies revealed that MCR could be related to cortical atrophy ( Blumen et al, 2021 ), lacunar infarction ( Wang et al, 2016 ), or increased levels of systematic inflammatory biomarkers ( Bortone et al, 2021 ). A cross-sectional study using MRI found that gray matter volumes, hippocampal volumes, and white matter hyperintensities were worse in individuals with MCR ( Yaqub et al, 2022 ). Meiner et al (2021) also reported that Apolipoprotein E ε4 allele (APOE ε4) was associated with the conversion to dementia in older adults with MCR.…”
Section: Introductionmentioning
confidence: 99%